2010
DOI: 10.1073/pnas.1002620107
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of human papillomavirus type-16 E6/E6* early mRNA is coupled to EGF signaling via Erk1/2 activation

Abstract: Certain types of human papillomaviruses (HPVs) are etiologically linked to cervical cancer. Their transforming capacity is encoded by a polycistronic premRNA, where alternative splicing leads to the translation of functional distinct proteins such as E6, E6*, and E7. Here we show that splicing of HPV16 E6/E7 ORF cassette is regulated by the epidermal growth factor (EGF) pathway. The presence of EGF was coupled to preferential E6 expression, whereas depletion of EGF, or treatment with EGF receptor (EGFR) neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 44 publications
4
87
1
Order By: Relevance
“…The functional interaction between the MAPK pathway and the activity of the Brm/Sam68 complex is also involved in the splicing of the human papillomavirus (HPV) polycistronic pre-mRNA. It was shown that EGF stimulated splicing of the E6 variant of HPV16, through a mechanism depending on activation of ERK1/2 and Brm/Sam68 (Rosenberger et al 2010). This observation suggests the involvement of Sam68 in the regulation of the life cycle of HPV and neoplastic transformation in cervical cancer.…”
Section: Role Of Sam68 In Alternative Splicingmentioning
confidence: 81%
“…The functional interaction between the MAPK pathway and the activity of the Brm/Sam68 complex is also involved in the splicing of the human papillomavirus (HPV) polycistronic pre-mRNA. It was shown that EGF stimulated splicing of the E6 variant of HPV16, through a mechanism depending on activation of ERK1/2 and Brm/Sam68 (Rosenberger et al 2010). This observation suggests the involvement of Sam68 in the regulation of the life cycle of HPV and neoplastic transformation in cervical cancer.…”
Section: Role Of Sam68 In Alternative Splicingmentioning
confidence: 81%
“…In HPV16, hnRNP A1 binds to an ESS in the L1 coding region and regulates HPV16 L1 RNA splicing (12,22). hnRNP A1 and A2 together were also proposed to regulate HPV16 E6 intron splicing (226^409 splicing) (19), but the mechanism of this regulation remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative RNA splicing of the HPV polycistronic pre-mRNAs plays a crucial role in regulation of viral gene expression (2,3). Although the molecular mechanisms that regulate alternative RNA splicing of bovine papillomavirus type 1 (BPV-1) (4-11) and HPV16 pre-mRNA transcripts (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) have been extensively studied in the past, a full transcription map of HPV18 in productive infection, the second most prevalent high-risk HPV genotype in association with cervical cancer (23), was constructed only recently (24), and the mechanistic regulation of HPV18 RNA splicing remains poorly investigated. HPV18 pre-mRNAs are transcribed mainly from a major early promoter, P 55/102 , or a major late promoter, P 811 , although a few other, weak promoters exist in the virus genome (24,25).…”
mentioning
confidence: 99%
“…HPV E5 protein mediates its carcinogenic effects using EGFR-dependent processes. [23][24][25][26] EGFR-directed therapies are effective treatments for some cancers associated with HPV infection. Reasons for the absence of a major clinical breakthrough in some patients may be multiple.…”
Section: Discussionmentioning
confidence: 99%